Marriage and Family Therapy Trainees' Reports of Explicit Weight Bias. (28th February 2015) - Pratt, Keeley J.; Palmer, Elizabeth; Cravens, Jaclyn D.; Ferriby, Megan; Balk, Elizabeth; Cai, Yin
Abstract : Discrimination based on an individual's weight has been observed in health care, education, retail, and other public sectors (Puhl & Huer, Obesity, 17, 941, 2007). Such inequity, known as "weight bias, " generates negative short‐term and long‐term consequences for the individuals that experience it (Puhl & Brownell, Weight bias in health care settings, 2007). Past research has shown that healthcare trainees exhibit weight bias (Phelan et al., Obesity, 22, 1201, 2014; Wigton & McGaghie, Journal of General Internal Medicine, 16, 262, 2001), yet little focus is given to weight bias in marriage and family therapy (MFT) education. The purpose of this study was to survey MFT students ( N = 162) to explore weight bias and how contextual factors associate with weight bias. Participants in MFT programs reported explicit weight bias, with specific contextual factors associating with more bias. Female participants reported more fear of gaining weight, and individuals who identified as overweight had higher rates of explicit weight bias. Contextual differences and implications for training programs are discussed.